Contemporary Methods for Preventing and Physically Rehabilitating Children with Cerebral Palsy - Shavkatovna, Ibragimova Malika; Farxadovna, Mavlayanova Zilola (American Journal of Bioscience and Clinical Integrity, 2025)
Cerebral palsy (CP) is a complex disorder of the central nervous system that not only affects motor function but also leads to intellectual developmental delays or impairments, speech difficulties, and sensory deficits such as hearing and vision impairments. Currently, the term "cerebral palsy" does not fully reflect the diversity and nature of neurological disorders associated with this condition. However, it remains widely used in global medical literature, as no alternative term comprehensively describing these pathological conditions has been proposed. The prevention of cerebral palsy includes both antenatal and postnatal measures. This article examines not only the pathogenetic aspects of cerebral palsy development but also describes its primary symptoms. It provides a list of preventive strategies aimed at reducing the incidence of cerebral palsy among children, as well as an overview of physical rehabilitation programs used for the treatment of affected patients.